2009
DOI: 10.1002/er.1534
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of direct expansion solar-assisted heat pumps using artificial neural networks

Abstract: SUMMARYArtificial neural network (ANN) is applied for exergy analysis of a direct expansion solar-assisted heat pump (DXSAHP) in the present study. The experiments were conducted in a DXSAHP under the meteorological conditions of Calicut city in India. An ANN model was developed based on backpropagation learning algorithm for predicting the exergy destruction and exergy efficiency of each component of the system at different ambient conditions (ambient temperature and solar intensity). The experimental data ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The ANN-predicted results obtained from LM11 (MLFFN using LM variant with eleven neurons in hidden layer) network configuration are used for thermodynamic performance simulation of a FCSAH using flat and pin-fin absorber plate. The optimal network parameters obtained in this work are similar to the earlier studies reported on modeling of solar air heaters [27], geothermal heat pumps [42] and solar-assisted heat pumps [43][44][45][46]. According to the above-mentioned studies, the MLFFN with LM variant and one hidden layer was identified as the good network configuration.…”
Section: Thermodynamic Performance Predictions Using Artificial Neuramentioning
confidence: 82%
See 1 more Smart Citation
“…The ANN-predicted results obtained from LM11 (MLFFN using LM variant with eleven neurons in hidden layer) network configuration are used for thermodynamic performance simulation of a FCSAH using flat and pin-fin absorber plate. The optimal network parameters obtained in this work are similar to the earlier studies reported on modeling of solar air heaters [27], geothermal heat pumps [42] and solar-assisted heat pumps [43][44][45][46]. According to the above-mentioned studies, the MLFFN with LM variant and one hidden layer was identified as the good network configuration.…”
Section: Thermodynamic Performance Predictions Using Artificial Neuramentioning
confidence: 82%
“…The process of combining the signals and generating the output of each connection is represented as mass. The three-layer feed-forward network is the widely used network configuration for energy and exergy performance predictions of renewable energy systems [42][43][44][45][46][47][48][49][50]. The network is trained with a suitable learning approach to perform a particular function by adjusting the mass coefficient values between processing neurons.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…A real technical revolution is needed to help the power industry to become cleaner than before. Solar energy aided power [6] or equipment [7] have been noticed and done some groping research works in the whole world.…”
Section: Introductionmentioning
confidence: 99%
“…The application of artificial neural network for the exergy performance prediction of solar adsorption refrigeration system working at different conditions is necessary nowadays for making the analysis simple. Many earlier studies have reported the application of artificial neural network for the performance predictions of vapour compression refrigeration systems such as for direct expansion heat pump [7], for modeling solar cooling systems [8], and for modeling cascade refrigeration systems [9] with the acceptable accuracy. Recently some works about the use of ANN in energy systems have been published [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%